Public perception towards factors that lead homelessness in Kota Kinabalu city / Ariani Hassin ... [et al.] - Hassin, Ariani; Idris, Nurjihad Asgari (2015)
The research is conducted at Kota Kinabalu City Sabah where I 00 respondents have involved. The specific location is Kampung Air, Segama, Sinsuran, and Gaya Street since it was frequent location of the homeless destitute at the area Kota Kinabalu . We conducted the research on public perception towards factors that lead to homelessness in Kota Kinabalu city. The public that lives around Kota Kinabalu city will be our respondents in order to get the information that can be used in our research. This section will discuss on differences among the socio-demographic factor (gender, age, race and education) of respondents on the perception towards factors that lead to homelessness. Our objectives are to analyze public perception towards homelessness and to investigate public perception towards factors that associated to the homelessness.